A new species of Henicocephaloides from Eastern Madagascar (Hemiptera: Heteroptera: Reduviidae) - Banar, P; Davranoglou, L; Chlond, D (BioOne, 2016)
Henicocephaloides raunoi sp. nov. (Hemiptera: Heteroptera: Reduviidae: Physoderinae) is described based on a single male specimen from Eastern Madagascar, which is deposited in the collection of the Moravian Museum, Brno. The newly described species is illustrated and compared to Henicocephaloides fulvescens Villiers, 1962. A revised generic diagnosis is also provided.